RESPON MORFOGENESIS EKSPLAN PUCUK ANGGREK TEBU (Grammatophylum speciosum Blume) SECARA IN VITRO TERHADAP BEBERAPA KONSENTRASI KINETIN - Ellok Dwi Sulichantini; Susylowati Susylowati; Ariya Ramadhan (Agrifor : Jurnal Ilmu Pertanian dan Kehutanan, 2020)
Sugarcane orchid (Grammatophyllum speciosum Blume) are known as a type of giant orchid, adult orchids can weigh 1 ton, panicle can grow up to 2.5 – 3 meters with a diameter of about 1.5-2 cm. Each panicle has dozens, even reaching one hundred flower buds, each with a diameter of about one 10 cm. Sugarcane orchids are a type of plant that is protected because its existence is increasingly scarce so that it needs in vitro propagation techniques to support its survival. To improve the growth of Grammatophyllum speciosum Blume in vitro shoot tip was growing on MS medium with varying concentration of kinetin (0, 1, 2, 3, and 4 mg L-1) with 5 replications. Shoot tip from in vitro culture around 1 cm lengt was used as explants. Observations carried out for 8 weeks after inoculation.The results showed that shoot explants tip  growth well in MS basic medium. The addition of kinetin to the medium, increases growth rate of culture. Increasing the concentration of kinetin tends to increase the growth. The best concentration for growth induction on plant height, stem diameter,  leaves length and  length of roots was 2 mg.L-1 kinetin, On the other hand 3 mg.L-1 kinetin gave best response on number of leaves and 4  mg.L-1 kinetin was the best concentration on leaves width and number of roots.